2021
DOI: 10.1261/rna.078929.121
|View full text |Cite
|
Sign up to set email alerts
|

A versatile tRNA modification-sensitive northern blot method with enhanced performance

Abstract: The ~22 mitochondrial and ~45 cytosolic tRNAs contain several dozen different posttranscriptional modified nucleotides such that each carries a unique constellation that complements its function. Many tRNA modifications are linked to altered gene expression and their deficiencies due to mutations in tRNA modification enzymes (TMEs) are responsible for numerous diseases. Easily accessible methods to detect tRNA hypomodifications can facilitate progress in advancing such molecular studies. Our lab developed a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
(142 reference statements)
1
3
0
Order By: Relevance
“…Another unexpected result concerns the nature of the correlation between mature suppressor tRNA levels and the degree of tRNA-mediated suppression activity, as has been posited to partially explain why the La protein promotes tRNA-mediated suppression (14). We found that the apparent increase in mature suppressor tRNA levels can at least partially be attributed to a decrease in modification at G26, supporting the idea of exercising caution when designing northern blotting probes to avoid sites of bulky modifications on the Watson-Crick face (34). Rather, our results point towards tRNA-mediated suppression activity as a function of the combination of suppressor tRNA levels and specific activity per suppressor tRNA molecule (Figure 3, Figure 4).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Another unexpected result concerns the nature of the correlation between mature suppressor tRNA levels and the degree of tRNA-mediated suppression activity, as has been posited to partially explain why the La protein promotes tRNA-mediated suppression (14). We found that the apparent increase in mature suppressor tRNA levels can at least partially be attributed to a decrease in modification at G26, supporting the idea of exercising caution when designing northern blotting probes to avoid sites of bulky modifications on the Watson-Crick face (34). Rather, our results point towards tRNA-mediated suppression activity as a function of the combination of suppressor tRNA levels and specific activity per suppressor tRNA molecule (Figure 3, Figure 4).…”
Section: Discussionsupporting
confidence: 69%
“…To investigate potential modification-independent functions of Trm1, we aligned an AlphaFold (32) prediction of S. pombe Trm1 to the structure of an archaeal Trm1 homolog bound to SAH (33), mutated an aspartic acid in the conserved catalytic site to alanine (D201A) (Figure 1C) and monitored Trm1-catalyzed modification of nuclear-and mitochondrially-encoded tRNAs with a northern blotting assay, positive hybridization in the absence of modification at G26 (PHA26) (19,34). This assay uses a probe complementary to the region overlapping G26, such that dimethylation at G26 impairs probe hybridization, resulting in a decrease in signal intensity.…”
Section: D201 Is a Key Catalytic Residue For N2 N2-dimethylation Of N...mentioning
confidence: 99%
“…As further validation for a role of TRMT1L in tyrosine tRNA modification, we employed the Positive Hybridization in the Absence of modification (PHA) assay (Arimbasseri et al , 2015; Khalique et al , 2022). This Northern blot-based assay relies on differential probe hybridization to tRNA caused by the presence or absence of m2,2G, which impairs base-pairing.…”
Section: Resultsmentioning
confidence: 99%
“…tRNA is also extensively modified with over 100 various modifications in three kingdoms of life. Current methods of detecting tRNAs and tRNA modifications include LC/MS (Suzuki and Suzuki 2014;Zhang et al 2022), northern blot (Zhang et al 2020;Khalique et al 2022), next-generation sequencing (Cozen et al 2015;Zheng et al 2015;Clark et al 2016), and end-ligation-based qPCR (Honda et al 2015b). A SplintR ligation-based qPCR method has been developed to detect and quantify microRNA (miRNA) (Jin et al 2016;Krzywkowski and Nilsson 2017).…”
Section: Resultsmentioning
confidence: 99%